Analisis Putusan MK No. 6/PUU-XXII/2024 tentang Uji Materi Undang-Undang Kejaksaan dalam Perspektif Teori Keadilan Wahbah Zuhaili - Fauziyah, Wiwin; Farkhani (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2024)
The Prosecutor's Office plays a vital role in law enforcement as a public prosecutor, contributing to the administration of justice. This study focuses on analyzing the Constitutional Court's Decision Number 6/PUU-XXII/2024 regarding the judicial review of Article 20 of the Prosecutor's Office Law through the lens of Islamic justice principles as proposed by Wahbah Zuhaili. Employing normative legal research methods with a statute and case approach, this study relies on library-based legal materials. The findings reveal two key points: First, the Constitutional Court partially upheld the Applicant's argument, basing its judgment on Article 1 paragraph (3), Article 24 paragraph (1), and Article 27 paragraph (1) of the 1945 Constitution, which address the qualifications for appointing the Attorney General, particularly concerning individuals affiliated with political parties. Second, from the perspective of Wahbah Zuhaili's concept of justice in Islam, the decision deviates from justice rooted in transcendental values derived from the Qur'an and Hadith, as it fails to promote social welfare and collective happiness